Development, implementation, and evaluation of a flagship simulation-based capstone course for graduating medical students in the Middle East - Dimassi, Zakia; Abuzitoon, Mohammed; Ahmad, Masood; Lutfi, Dana; Vijayakumar, Thripti; Kakati, Nora; Murray, David; Guraya, Salman (Frontiers in Medicine, 2025)
BackgroundTransitioning from undergraduate to graduate medical education is characterized by challenges related to clinical competence, professional identity formation, and the adoption of system-based practice. This transition serves as an accountability measure for medical schools, particularly for international medical graduates (IMGs). Unfortunately, there remains a gap in medical education that may compromise the fitness to practice of graduating doctors. To address this gap, this work aimed to develop, implement, and evaluate a simulation-based Transition to Residency (TTR) capstone course within a Doctor of Medicine (MD) course that aligns with the Entrustable Professional Activities (EPAs) and specifically targets the educational shortcomings experienced by new medical graduates.MethodsOur course adopted the modified Kern 7-step approach and incorporated simulation-based, Kolb’s experiential learning, and e-learning constructs. The core themes included patient safety, basic and advanced procedural skills, “night on call,” acute case management training, and life support training. The main themes were mapped to high-yield competencies that corresponded with the core EPAs. A structured study plan, clear learning objectives, assessment tools, and full integration of educational and simulation technologies were developed. The pre- and post-data regarding students’ self-assessment of competence, their performance assessment (Kirkpatrick’s level 2), and their satisfaction with the learning outcomes (Kirkpatrick’s level 1) were analyzed.ResultsThe success of this course was evident in the high student satisfaction rates and the overall increase in their self-assessment of skill acquisition across domains in all 3 years, with persistently highest improvements in the psychomotor domain (p < 0.001 and Cohen’s d = 1.02, 2.29, and 1.44) compared to cognitive and communication domains. From a course organization standpoint, centralizing communication, appointing independent assessors, managing workload, and digitizing all procedures mitigated several challenges faced.DiscussionOur study highlights systematic implementation strategies, potential challenges, sustainability concerns, and future recommendations of a flagship capstone course, including the development of residency-specific training options. The high satisfaction rates and documented enhancement in all competency domains of the capstone course affirm its role in bridging gaps in medical education.